PENERAPAN MODEL ROLE PLAYING DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SEKOLAH DASAR - Ulpi Aprilia; Rusdial Marta; Fadhilaturrahmi, Fadhilaturrahmi; Nurhaswinda, Nurhaswinda; M. Syahrul Rizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low problem solving abilities of students in Mathematics learning in class V SDM 014 Payung Island. One solution to overcome this problem is to apply the Role Playing model. The aim of this research is to improve students' problem solving abilities in Mathematics learning. The research method used by researchers is Classroom Action Research (PTK), which is carried out in two cycles, each cycle consisting of 2 meetings and 4 stages, namely planning, implementation, observation and reflection. The research was carried out in September 2024. The subjects of this research were 24 students in class V of SDM 014 Payung Island, consisting of 18 men and 6 women. Data collection techniques include documentation and observation. This is before any action is taken, the student's problem solving ability is 29.16%. After taking action in cycle I it increased to 62.5%. Meanwhile in cycle II it increased to 91.66%. Thus, it can be concluded that using the Role Playing learning model can improve problem solving abilities in Mathematics learning at SDM 014 Pulau Payung.